2003
DOI: 10.1016/s0308-521x(02)00074-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of personal information sources on the decision-making process of Costa Rican dairy farmers

Abstract: The attitudes of farmers in relation to the importance of different people as information and opinion sources (InfS) for different phases of the decision-making process were studied in 91 Costa Rican dairy farmers. The InfS studied were: Family members, Other farmers, Technical advisors, Farm staff and Commercial agents, while the phases were: Problem detection, Seeking for problem solutions, Seeking for new practices and Seeking for opinion. A Multidimensional Preference Analysis (MDPREF) was used to obtain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 9 publications
5
57
1
8
Order By: Relevance
“…Formal and informal networks of information-sharing relationships between individuals and groups play important roles in the facilitation of natural resource management, the encouragement or prevention of changes in land use, agricultural innovation, and the diffusion and adoption of farming practices (Bodin et al 2006;Cadger et al 2016;Conley and Udry 2001;Demiryurek 2010;Hoang et al 2006;Isaac 2012;Isaac et al 2014;Klerkx et al 2010;Leeuwis 2004;Matous and Todo 2015;Matouš et al 2013;Prell et al 2009Prell et al , 2010Rogers 2003;Solano et al 2003;Spielman et al 2009Spielman et al , 2011Tengö and Belfrage 2004).…”
Section: Theoretical Framework: Social Network and Spatially Distribmentioning
confidence: 99%
“…Formal and informal networks of information-sharing relationships between individuals and groups play important roles in the facilitation of natural resource management, the encouragement or prevention of changes in land use, agricultural innovation, and the diffusion and adoption of farming practices (Bodin et al 2006;Cadger et al 2016;Conley and Udry 2001;Demiryurek 2010;Hoang et al 2006;Isaac 2012;Isaac et al 2014;Klerkx et al 2010;Leeuwis 2004;Matous and Todo 2015;Matouš et al 2013;Prell et al 2009Prell et al , 2010Rogers 2003;Solano et al 2003;Spielman et al 2009Spielman et al , 2011Tengö and Belfrage 2004).…”
Section: Theoretical Framework: Social Network and Spatially Distribmentioning
confidence: 99%
“…Previous research has shown that the lack of social learning and interpersonal information exchange can result in a lack of awareness and the non-adoption of resourceconserving agricultural practices (Solano et al 2003;Schneider et al 2009;Janssen et al 2006;Pretty and Smith 2004;Bodin and Crona 2009;Bodin and Prell 2011;Leeuwis 2004;Hoang et al 2006;Isaac 2012;Isaac et al 2007;Spielman et al 2011;Conley and Udry 2010). Thus, limiting farmers' mobility may decrease farmers' access to new beneficial techniques in other communities, and farmers may in turn use less-informed and even environmentally harmful practices.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of formal institutions in disseminating necessary agricultural information across vast underdeveloped rural regions has been questioned (Matouš et al 2013b;Douthwaite et al 2001;Leeuwis 2004;Warner 2007;Spielman et al 2009;Gebremedhin and Swinton 2003), and informal social networks and social contact have been recognized as important channels for information-sharing about resource-conserving practices (Rogers 2003;Solano et al 2003;Schneider et al 2009;Ostrom 1990;Folke 2006;Janssen et al 2006;Pretty and Smith 2004;Bodin and Crona 2009;Bodin and Prell 2011;Leeuwis 2004;Hoang et al 2006;Isaac 2012;Isaac et al 2007;Warner 2007;Spielman et al 2011;Conley and Udry 2010;Bartholomay et al 2011). However, communication connections among the inhabitants of areas with less developed infrastructures tend to be geographically constrained, and the potential for the diffusion of beneficial practices between communities is thus limited (Matous et al 2013a;Apicella et al 2012;Urry 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Farm management research is focused more on describing farmers' decision-making processes and decision outcomes than on information management issues, which are generally dealt with indirectly through the analysis of farmers' decision-making processes: 'information is an input required in every step of the decision-making process, that is, goal formulation, problem recognition, problem formulation (identifying the causes of problems), preselection of alternative actions, and in more general terms, in uncertainty reduction' (Timko and Loynes, 1989;Solano et al, 2003). According to McCown (2002), decision support systems (DSSs) are information systems (ISs), and like them 'were designed to serve functions deemed by ''management scientists'' to be potentially useful to managers'.…”
Section: Introductionmentioning
confidence: 99%